A computational study on mixed convection in a porous media filled and partially heated lid-driven cavity with an open side - Abu-Hamdeh, Nidal H.; Öztop, Hakan Fehmi; Alnefaie, Khalid A. (Elsevier, 2020)
Applications of mixed convection due to lid-driven cavities can be found in different engineering technologies. A computational study was conducted to explore the effects of different parameters on mixed convection in a porous media filled lid-driven cavity with one side opening in the presence of heat generation. The cavity has a flush mounted heater on its bottom wall. The governing equations were solved by developing a computer code by using finite volume technique for different parameters as length of heater (1/5, 2/5, 4/5), Richardson number (0.1, 1, 10) and Darcy number (0.1, 0.01, 0.001). It is found that heat transfer and flow field inside the cavity is so complex due to moving lid, open side wall and heater. Heat transfer increases with increasing of Grashof numbers, heater length and decreased with Darcy numbers. (C) 2020 The Authors. Published by Elsevier B.V. on behalf of Faculty of Engineering, Alexandria University.
Keywords: Lid-driven cavity; Porous; Open cavity; Partial heating; Finite volume technique